Optimization Analysis of Over-Sized Section Open-Off Cut Failure and Support - Shi, Jianjun; Feng, Jicheng; Rui, Peng; Zhu, Quanjie (Geotechnical and geological engineering, 2020)
The open-off cut section of 1105 working face in Zhaogu II mine is the largest in China, causing considerable difficulties to the support work. The failure process of surrounding rock deformation, stress field, and stress state under original support of open-off cut is analyzed using FLAC3D numerical simulation analysis software. Analysis results show the large displacement of the bottom heave and two sides of the roadway. Furthermore, the vertical stress of open-off cut is greater than the horizontal stress, whereas horizontal stress is larger in the upper roof part. The shearing failure range of the open-off cut surrounding rock is large, indicating that the original support scheme possesses weak restraint capability to the surrounding rock and fails to effectively control deformation. Based on analysis and research results, the technical scheme of coordinated support for super-long anchor rod and anchor cable of over-sized section open-off cut with high-stress broken surrounding rock is put forward. The field industrial test shows that the coordinated support scheme of super-long anchor rod and anchor cable is reasonable and safe under a 9.2 m open-off cut section. With improvement of the working face, the deep rock layer on the roof at the open-off cut position of goaf first occurs evidently, whereas the shallow rock layer is unremarkable, indicating the stable rock formation in the anchorage area of the shallow super-long anchor. The super-long anchor rod plays a satisfactory role in support, and the control effect of broken surrounding rock is similarly satisfactory. Such condition can achieve large deformation of broken surrounding rock with high stress and super large section.